A Parallel Mediation Model of Career Adaptability, Career Self-Efficacy, and Future Career Choice Among University Students: The Role of Basic Psychological Needs Satisfaction and Mindfulness - Girum Tareke Zewude; Anmut Endalkachew Bezie; Getachew Tassew Woreta; Tsehaynew Getaneh Tareke; Tun Zaw Oo; Ayalew Hassen; Merkebu Tareke; Yvette Orsovics; Krisztián Józsa (European Journal of Investigation in Health, Psychology and Education)
This study aims to explore the importance of basic psychological needs satisfaction (BPNS) and mindfulness of university students in their career adaptability (CA), career self-efficacy (CSE), and future career choice (CC). The sample consisted of 1026 undergraduate students, of which 495 (48.2%) were female and 531 (51.8%) male, from three public universities in the Amhara Region, Ethiopia. The assessments, such as the Career Decision-Making Self-Efficacy Scale-Short Form, the Five Facet Mindfulness Questionnaire Short Form, the Career Adapt-Ability Short Form Five Scale, the Basic Psychological Needs Satisfaction Scale, and the Career Choice scale instruments were used. Findings from a parallel mediation model showed that both CA and CSE had a direct positive effect on the BPNS of university students. Additionally, this study found that both BPNS and mindfulness had a substantial and positive direct effect on the students’ CC. Importantly, we found that both CA and CSE significantly and indirectly predicted the future CC through BPNS and mindfulness. In addition, BPNS and mindfulness also partially mediate the relationship between CA, CSE, and the students’ future CC. Importantly, we found that mindfulness and BPNS fully and partially mediated the relationship between CA, CSE, and CC. These results support the notion that both psychological constructs (BPNS and mindfulness) play a crucial role in explaining the relationship between CA, CSE, and CC. By enhancing students’ BPNS and mindfulness, institutions can empower students to make informed decisions about their future career paths, ultimately nurturing their personal and professional growth.